A Study of Taiwanese Teens' Traditional and Cyberbullying Behaviors. (June 2014) - Yang, Shu Ching; Lin, Chia-Ying; Chen, An-Sing
This study examined several types of teen behaviors, specifically bullying, being bullied, and witnessing bullying, and analyzed teens' judgments of the seriousness of the bullying. A Bullying Behaviors Scale (BBS) was designed to investigate both traditional bullying (TB) and cyberbullying (CB) behaviors among teens in grades 5 through 11. The study also explored the prevalence of both types of bullying according to gender and grade. Descriptive statistics revealed that TB and CB were moderately prevalent among teens, with CB occurring less frequently than traditional bullying. Verbal bullying was the most common form of TB for victims, bullies, and bystanders, followed by relational and physical bullying. Bullying events were found to be more prevalent among boys than girls and were more frequently experienced by older children than younger children for almost all types of TB and CB. The only exception was physical bullying, whose victims tended to be younger. The study concludes by discussing suggestions for further research.